Characterization of the gas releasing behaviors of catalytic pyrolysis of rice husk using potassium over a micro-fluidized bed reactor. (15th March 2017) - Liu, Yuan; Wang, Yan; Guo, Feiqiang; Li, Xiaolei; Li, Tiantao; Guo, Chenglong; Chang, Jiafu
Highlights: Releasing propensity of CO, CO2, CH4 and H2 was studied in a micro-fluidized bed. Gas releasing pattern was influenced by temperature and potassium concentration. Variations in gas forming Ea are indicative of catalytic performance of potassium. Abstract: Influence of potassium on the gas releasing behaviors during rice husk high-temperature pyrolysis was investigated under isothermal conditions in a two stage micro-fluidized bed reactor. Reaction kinetics for generating H2, CO, CO2 and CH4 was investigated based on the Friedman and model-fitting approaches. Results indicated that different gas species had different times to start and end the gas release process, particularly at 600 °C, representing different chemical routes and mechanics for generating these gas components. The resulting apparent activation energies for H2, CO, and CO2 decreased from 23.10 to 12.00 kJ/mol, 15.48 to 14.03 kJ/mol and 10.14 to 7.61 kJ/mol respectively with an increase in potassium concentration from 0 to 0.5 mol/kg, while that for CH4 increased from 16.85 to 19.40 kJ/mol. The results indicated that the addition of potassium could promote the generation reactions of H2, CO and CO2 while hinder the generation reactions of CH4 . The pyrolysis reaction was further found to be subject to the three-dimensional diffusion model for all the samples.